Penerapan Augmented Reality pada Pembelajaran Kimia: Tinjauan Sistematis - Rifki Nomizar Khairani; A. K. Prodjosantoso (Jurnal Penelitian Pendidikan IPA, 2023)
The rapid development of technology in the world of education has many positive impacts, namely facilitating the learning process. Technological sophistication can be felt, one of which is augmented reality. This Augmented Reality concept collaborates the real world with the virtual world which can display more detailed information in 3D visuals. This review systematic analysis study was conducted to classify the application of augmented reality in chemistry learning. The main criteria for the selections of journals the implementation of augmented reality in the field of chemistry education with a period ranging from 2015 to 2022 from an international database. There were 74 journals were obtained that fit into the criteria. Journal studies focused on the application of AR chemistry materials at the high school and university levels. The studies analyzed focused on the form of applying AR in chemistry learning, applied chemistry, chemical material, and sample level. The results of the study show that the application of AR in chemistry learning is often presented in the form of android-based learning, organic chemistry is widely applied using AR. In addition, an explanation of the application of chemical concepts and sample groups is also discussed here.